PARTISIPASI POLITIK PEREMPUAN DALAM PEMILIHAN KEPALA DESA DI DESA BABOTIN MAEMINA KECAMATAN BABOTIN LEOBELE KABUPATEN MALAKA - Bria, Fridolino Stefen; Trifosa Tes, Maria; Selviana Bere, Jeni; Edelreda Fitun, Maria; Tefa, Dagunda; Walde Klau, Marlin; S. Kolo, Selfridiana (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
This report examines women's political participation in the Village Head Election (Pilkades) in Babotin Maemina Village, Babotin Leobele Subdistrict, Malaka Regency. The study focuses on the low level of female participation as candidates and voters. Using a qualitative approach, it identifies factors such as patriarchal cultural norms, lack of political education, and low self-confidence among women. Despite governmental socialization efforts, male candidates continue to dominate. The study recommends empowering women politically through political education programs, creating platforms for women's aspirations, and involving women in village policy-making processes to enhance gender equality and local democracy.